A Balancing Act: Renee Houston – A Career in Film and the Variety Stage. Issue 3 (2nd September 2019) - Gates, Sam
Abstract : Between the two great wars the British variety theatre and film developed a complex interrelationship in which performers negotiated new challenges: emerging technologies, strong management structures and fierce competition. Taking the career of Renee Houston (1902–80) as a case study, this article details her comedy double act with her sister (Billie) in drag. The Houston Sisters worked their way from local cine-variety to national fame on radio, the live stage and film, while Renee's subsequent solo career mapped the trajectory of popular entertainment in a period which introduced modernism, talking pictures, radio broadcasting and greater freedom of expression for women.